Assessing prognosis with modified early warning score, rapid emergency medicine score and worthing physiological scoring system in patients admitted to intensive care unit from emergency department - Gök, Raziye Gizem Yüksel; Gök, Alper; Bulut, Mehtap (Elsevier, 2019)
Introduction: In this study our purpose is to examine the effectiveness and reliability of MEWS (Modified Early Warning Score), REMS (Rapid Emergency Medicine Score) and WPS (Worthing Physiological Scoring System) scoring systems for prediction of the prognosis and mortality rate of critically ill patients scheduled to be admitted to intensive care unit (ICU) among emergency department (ED) patients. Methods: This single-centered retrospective study was performed on medical, surgical and trauma patients referred to the ED and admitted to ICU of University Hospital between 23 July 2013 and 26 November 2015. Results: Mortality and the duration of stay in ICU were significantly correlated with systolic blood pressure (SBP) and WPS score compared to other variables (p = 0.014, p = 0.010 respectively). The decrease in SBP increased the mortality by 2 (OR: %95 CI 1.1-3.5) fold and the increase in WPS increased the mortality by 2.4 (OR: %95 CI 1.2-4.5) fold. Conclusions: In our study, there was a more significant correlation between WPS score and mortality and duration of stay in ICU compared to other scores.
Keywords: ED; ICU; MEWS; REMS; WPS; SBP